Project-Based Learning in English Language Teaching: A Bibliometric Exploration - Salam, Naimul; Kolopita, Alisa Alicia; Akhmad, Zulkifli (English Education Department, 2024)
This bibliometric study aims to analyze the trends and developments in PBL research within the field of ELT by examining scholarly publications from the past decade. Using data from prominent academic databases such as Sinta and Google Scholar, this study maps the evolution of PBL research, identifies key publications and authors, and highlights emerging research themes and methodologies. The analysis reveals a notable increase in the number of publications on PBL, with a significant surge in 2022. This rise is indicative of a growing interest in innovative teaching methods, potentially driven by the challenges and changes brought about by the COVID-19 pandemic. The study finds a predominant use of qualitative research methods, including observations and interviews, which offer in-depth insights into the practical application and impact of PBL. Research subjects primarily consist of students and teachers, though there is a limited focus on junior high school students, suggesting areas for future exploration. Data collection instruments employed across the studies include observations, questionnaires, interviews, and pre-tests/post-tests, reflecting a diverse methodological approach. The topics covered by the reviewed articles span various aspects of English language learning, such as English for Specific Purposes (ESP), metacognitive abilities, and spoken English. These findings underscore PBL's versatility and its potential to enhance specific language skills. In conclusion, the bibliometric analysis highlights the dynamic nature of PBL research in ELT, demonstrating its growing significance and the continued potential for refining educational practices through this innovative approach.